Anion Binding Studies of Urea and Thiourea Functionalized Molecular Clefts - Manna, Utsab; Portis, Bobby; Egboluche, Tochukwu K.; Nafis, Muhammad; Hossain, Md. Alamgir (Frontiers in Chemistry, 2021)
Two rationally designed 4-nitrophenyl-based molecular clefts functionalized with thiourea (L1) and urea (L2) have been synthesized and studied for a variety of anions by UV-Vis and colorimetric techniques in DMSO. Results from the binding studies suggest that both L1 and L2 bind halides showing the order: fluoride > chloride > bromide > iodide; and oxoanions showing the order: dihydrogen phosphate > hydrogen sulfate > nitrate > perchlorate. Each receptor has been shown to form a 1:1 complex with an anion via hydrogen bonding interactions, displaying distinct color change for fluoride and dihydrogen phosphate in solution. As compared to the urea-based receptor L2, the thiourea-based receptor L1 exhibits stronger affinity for anions due the presence of more acidic thiourea functional groups.